SOCIOCULTURAL CHARACTERISTICS OF SPEECH BEHAVIOUR OF TEENAGERS FROM THE GENDER POSITION - Ismagulova, G.; Ismailova, А. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2021)
Relevance: This article examines the characteristics of the conversational style of speech of adolescents, due to social factors. The article analyzes the differences in the speech behavior of boys and girls, depending on the gender influence caused by social factors and presents visual samples showing the indispensable influence of sociocultural factors on the speech behavior and style of adolescents. In connection with the rapidly growing pace of social development of society, the modernization of education, it is believed that sexual differentiation is directly related to language, and in linguistics it is given more attention, thanks to recent works that have created a rich basis for building a theoretical model of male and female speech behavior. The study of speech behavior of adolescents from the perspective of gender is an actual and significant phenomenon, since it is in adolescence that the norms, rules and values of gender culture are assimilated, in which socially determined ideas about the specificity of female and male speech behavior have already been created. Goal: The purpose of this work is to identify and justify the differences in the gender characteristics of male and female speech.
Keywords: gender linguistics; speech; speech behavior; conversational style; gender; gender factor; male and female speech